SIGNIFIKANSI HARGA, FASILITAS DAN LAYANAN TERHADAP KEPUASAN KONSUMEN JASA HOTEL - Hery Purnomo; Rino Sardanto; Basthoumi Muslih (STIE Muhammadiyah Jakarta, 2021)
The purpose of this research is to know how much the significance of the price, facilities and services have been conducted, influence consumer satisfaction, either partially or simultaneously. Research using quantitative descriptive approaches, and rules for collecting information on poll use, where data analysis techniques with multiple regression analysis methods. Sample size in research of 80 respondents, with sampling method using probability sampling ordinance. The results found that prices, facilities and services are partially and simultaneously have significance to consumer satisfaction, during the Covid-19 pandemic. These results show that Hotel management needs to consider how facilities and employee interactions with Hotel consumers can be managed to satisfy consumer satisfaction, which will take them to receive premium prices charged by the Hotel. This study will allow the Lotus Garden Hotel Resort to be even better.